Comparison of clinical performance of antigen basedenzyme immunoassay (EIA) and major outer membrane protein (MOMP)-PCR for detection of genital Chlamydia trachomatis infection - Mahmoud Nateghi Rostami; Batool Hossein Rashidi; Fatemeh Aghsaghloo; Razieh Nazari (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Chlamydia trachomatis is the most common sexually transmitted bacterial pathogen worldwide. Early detection and treatment of C.trachomatis genital infection prevent serious reproductive complications. Objective: Performances of enzyme immunoassay (EIA) and major outer membrane protein (MOMP)-polymerase chain reaction (PCR) for diagnosis of genital C.trachomatis infection in women were compared. Materials and Methods: In this cross sectional study a total of 518 women volunteers were included (33.67±8.3 yrs) who had been referred to Gynecology clinics of Qom province, Iran, were included. Endocervical swab specimens were collected to detect lipopolysaccharide (LPS) antigen in EIA and to amplify MOMP gene of C.trachomatis in PCR. Results were confirmed using ompI nested-PCR. Sensitivity, specificity, positive (PPV) and negative predictive values (NPV) were calculated for performance of the tests. Odds ratios were determined using binary logistic regression analysis. Results: In total, 37 (7.14%) cases were positive by EIA and/or MOMP-PCR. All discrepant results were confirmed by nested-PCR. Sensitivity, specificity, PPV and NPV values of EIA were 59.46%, 100%, 100% and 96.98%, and those of MOMPPCR were 97.30%, 100%, 100%, 99.79%, respectively. Reproductive complications including 2.7% ectopic pregnancy, 5.4% stillbirth, 5.4% infertility, and 10.8% PROM were recorded. The risk of developing chlamydiosis was increased 4.8-fold in volunteers with cervicitis (p<0.05; OR 4.80; 95% CI 1.25-18.48). Conclusion: C.trachomatis infection should be regarded in women of reproductive ages especially those with cervicitis. Primary screening of women by using the low cost antigen-EIA is recommended; however, due to the low sensitivity of Ag-EIA, verification of the negative results by a DNA amplification method is needed.